Analisis Sifat Kimia Kayu Meranti Tembaga (Shorea leprosula Mig.) Dari Hutan Alam Dan Hutan Tanaman Di PT. Dwima Jaya Utama : Chemical Properties Analysis of Meranti Tembaga Wood (Shorea leprosula Mig.) from Natural Forests and Plantation Forests at PT. Dwima Jaya Utama - Joni, Herwin; Santoso, Mahdi; Wahyudi, Wahyudi; Sosilawaty, Sosilawaty; Tanduh, Yusintha; Triyadi, Antonius; Toni, Hendra; Christy, Eva Oktoberyani; Silvianingsih, Yosefin Ari (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
This study analyzes the chemical properties of Meranti Tembaga wood (Shorea leprosula Mig.) from natural forests and intensively managed plantation forests (Silin) at PT. Dwima Jaya Utama. Samples were taken from trees with diameters of 28 cm, 36 cm, 43 cm, and 51 cm to compare extractive content (cold water, hot water, ethanol-toluene), holocellulose, α-cellulose, lignin, and ash levels. Results showed that Silin-grown wood had higher extractive content in cold and hot water but lower lignin and ash levels compared to natural forest wood. α-Cellulose content was consistently high across all diameters, meeting industrial standards. The findings suggest that Silin techniques can produce quality wood with shorter harvest cycles, though chemical properties vary by diameter and origin. This research provides valuable insights for sustainable forest management and industrial applications of Shorea leprosula.